2015
DOI: 10.1038/mp.2015.135
|View full text |Cite|
|
Sign up to set email alerts
|

Citalopram and sertraline exposure compromises embryonic bone development

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are the most commonly prescribed treatments for depression and, as a class of drugs, are among the most used medications in the world. Concern regarding possible effects of SSRI treatment on fetal development has arisen recently as studies have suggested a link between maternal SSRI use and an increase in birth defects such as persistent pulmonary hypertension, seizures and craniosynostosis. Furthermore, SSRI exposure in adults is associated with decreased bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…These drugs reduced bone mineralization and decreased osteoblast markers during embryogenesis. In differentiation process of human mesenchymal stem cells, decreasing the activity of osteoblasts and reducing the expression of RUNX2 and ALP genes were observed . In the study of Fraher, the cells types were similar to those of our study, but they evaluated other drugs of SSRI class that their results were in consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These drugs reduced bone mineralization and decreased osteoblast markers during embryogenesis. In differentiation process of human mesenchymal stem cells, decreasing the activity of osteoblasts and reducing the expression of RUNX2 and ALP genes were observed . In the study of Fraher, the cells types were similar to those of our study, but they evaluated other drugs of SSRI class that their results were in consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 89%
“…They showed that citalopram increases the expression of OCN and ALP in osteogenesis and causes cranio-facial defects by modifying the bone property of mouse calvarial pre-osteoblast cells [36]. Our results were paralleled with the study of Bradaschia et al which was conducted on osteogenic In differentiation process of human mesenchymal stem cells, decreasing the activity of osteoblasts and reducing the expression of RUNX2 and ALP genes were observed [37]. In the study of Fraher, the cells types were similar to those of our study, but they evaluated other drugs of SSRI class that their results were in consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 85%
“…We thus included concentrations that are similar to the doses used in animal model systems and doses prescribed for human use, as well as lower concentrations. For a comparison of concentrations in other species we refer to (Fraher et al, 2016; GlaxoSmithKline, 2017; Lilly, 2009; Lu et al, 2008; Lu et al, 2006; Pfizer, 2002; Vermoesen et al, 2011). On days larvae were not treated, all groups were housed in egg water.…”
Section: Methodsmentioning
confidence: 99%
“…Although sertraline is considered a safe drug, several reports have associated it with toxic effects on the liver [1416] and hepatic cells [2, 13, 17]. Recently, cardiac toxicity has been related to sertraline, even in therapeutic doses [18, 19], and its use during pregnancy was associated with an increased risk of major malformations [20] and compromise of embryonic bone development [21]. …”
Section: Introductionmentioning
confidence: 99%